Intertrack interaction at ultra-high dose rates and its role in the FLASH effect - Baikalov, Alexander; Abolfath, Ramin; Schüler, Emil; Mohan, Radhe; Wilkens, Jan J.; Bartzsch, Stefan (Frontiers in Physics, 2023)
The mechanism responsible for the FLASH effect remains undetermined yet critical to the clinical translation of FLASH radiotherapy. The potential role of intertrack interactions in the FLASH effect, arising from the high temporal concentrations of particle tracks at UHDRs, has been widely discussed but its influence remains undetermined.We construct an analytical model of the distribution, diffusive evolution, and chemical interaction of particle tracks in an irradiated target. We fit parameters of the model to Monte Carlo (MC) simulations of electron tracks, and include the effects of scavenging capacities of different target media. We compare the model's predictions to MC simulations of many interacting electron tracks, and use the comparison to predict the prevalence of intertrack interactions in the parameter space where the FLASH effect is observed in vivo, and where differential reactive species (RS) yields have been observed in aqua.Results: MC simulations of interacting electron tracks demonstrate negligible changes in RS yields at 12 Gy both in oxygenated water and in cellular scavenging conditions, but significant changes at 58 Gy in oxygenated water. The model fits well to the simulation data, and predicts that pulse doses > 90 Gy delivered in 0.5 µs would be necessary for intertrack interactions to affect RS yields in cellular scavenging conditions, and > 13 Gy in 0.5 µs for water at 4% O 2 . The model defines optimal beam parameters (e.g., dose, pulse width, LET) to maximize intertrack interactions, and indicates that decreasing the pulse width of electron pulses further below ≈ 0.5 µs has no effect on intertrack interactions.The results of the MC simulations indicate that intertrack interactions do not play a role in the parameters space where the FLASH effect is observed. However, potentially critical limitations in the simulations performed provide the possibility that intertrack interactions occur much more readily than predicted. More accurate simulations, as well as experimental characterization of RS yields across the pulse parameter space, are necessary to more confidently Baikalov et al. confirm or deny the role of intertrack interactions in the FLASH effect.